2019
DOI: 10.1051/0004-6361/201834665
|View full text |Cite
|
Sign up to set email alerts
|

2D chemical evolution model: The impact of Galactic disc asymmetries on azimuthal chemical abundance variations

Abstract: Context. Galactic disc chemical evolution models generally ignore azimuthal surface density variation that can introduce chemical abundance azimuthal gradients. Recent observations, however, have revealed chemical abundance changes with azimuth in the gas and stellar components of both the Milky Way and external galaxies. Aims. To quantify the effects of spiral arm density fluctuations on the azimuthal variations of the oxygen and iron abundances in disc galaxies. Methods. We develop a new 2D galactic disc che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 79 publications
8
53
0
Order By: Relevance
“…NGC 628 and NGC 2835 show some regular azimuthal variations, but they do not correspond to the peaks in star formation. One significant difference between this study and previous work is our focus on the inner portions of the disk (R<0.5 R 25 ), whereas some recent theoretical work has suggested that azimuthal trends should be more pronounced in the outer disks near the corotation radius, where the relative velocity with respect to the pattern speed of the disk is close to zero (Spitoni et al 2019). Sánchez-Menguiano et al (2019) carried out a detailed investigation of the local relation between star formation rate and metallicity, where for both quantities a radial relation has been removed.…”
Section: Subtle Evidence For Azimuthal Variationsmentioning
confidence: 62%
“…NGC 628 and NGC 2835 show some regular azimuthal variations, but they do not correspond to the peaks in star formation. One significant difference between this study and previous work is our focus on the inner portions of the disk (R<0.5 R 25 ), whereas some recent theoretical work has suggested that azimuthal trends should be more pronounced in the outer disks near the corotation radius, where the relative velocity with respect to the pattern speed of the disk is close to zero (Spitoni et al 2019). Sánchez-Menguiano et al (2019) carried out a detailed investigation of the local relation between star formation rate and metallicity, where for both quantities a radial relation has been removed.…”
Section: Subtle Evidence For Azimuthal Variationsmentioning
confidence: 62%
“…Based on the conclusions reached by previous works, we find that the complementarity of the analysis of the chemical distribution presented here with a future analysis on the gas velocity distribution for the same galaxy sample could be key in order to investigate the existence of radial flows in these galaxies and their connection with the observed arminterarm abundance distributions. Furthermore, the analysis on the velocity pattern would enable the derivation of the corotation radius location, in order to confirm theoretical predictions finding stronger abundance variations close by these regions (Spitoni et al 2019). Both aims will be addressed in a forthcoming paper.…”
Section: Discussionmentioning
confidence: 88%
“…Recent two-dimensional chemical evolution models also predict azimuthal structure in the gas-phase oxygen abundance. For example, Spitoni et al (2019) find that density fluctuations due to spiral arms produce oxygen abundance variations on the order of ∼0.1 dex, with the most azimuthal structure apparent at and beyond the corotation radius. The magnitude of these abundance fluctuations decreases with time as the model galaxy becomes well-mixed.…”
Section: Discussionmentioning
confidence: 99%